Dynamic changes in mental health status related to the COVID-19 pandemic among health care workers and inpatients in China - Tong, Yujun; Zhang, Qian; Wang, Xiaoran; Du, Yanlin; Chang, Dong; Cui, Yong; Duan, Xinchun (Frontiers in Psychiatry, 2022)
Background Exposure to coronavirus disease 2019 (COVID-19) can cause severe mental health problems, the dynamics of which remain unclear. This study evaluated the mental status of frontline health care workers (FHWs) and suspected infected patients (SIPs) during different periods of the COVID-19 outbreak. Materials and methods Demographic and psychological data were collected through a cross-sectional survey of 409 participants in a hospital from 20 January to 7 August 2020. COVID-19 outbreaks were divided into three periods owing to the time, place, and scale, including the national outbreak period (a nationwide pandemic period from 20 January to 8 April 2020), sporadic period (a stable period from 9 April to 10 June), and local epidemic period (a local pandemic in Beijing from 11 June to 7 August 2020). Acute psychological disorders (APDs), including symptoms of anxiety and depression, were assessed using the Zung Self-Rating Anxiety/Depression Scale (SAS/SDS). Results A total of 206 FHWs and 203 SIPs completed the electronic questionnaire. Overall, the prevalence rates of anxiety and depression among SIPs were 3.9 and 19.4%, respectively, while significantly higher prevalence rates (17.7 and 25.1%) were found among FHWs, P-value < 0.05. Psychological status among SIPs did not differ significantly across the three periods. The FHWs were more vulnerable, as their SAS and SDS scores and almost all the dimension scores were significantly higher during the local epidemic period than during the national outbreak and sporadic periods (all P-values < 0.001). The prevalence of anxiety (34.41%) and depression (41.94%) was significantly higher during the local epidemic period (P < 0.001). Logistic and linear mixed models showed that age, sex, and doctor-patient ratio especially, independently influenced most dimension scores of SAS and SDS among FHWs (P < 0.05). Conclusion Compared to the COVID-19 epidemic at the national level, the local epidemic had a greater influence on FHWs’ mental health. More attention should be given to the workload of FHWs.